Business Ownership and Unemployment in Japan - Joost van Acht; Joop Stam; Roy Thurik; Ingrid Verheul (Tinbergen Institute, 2004)
The influence of industrial structure, more specifically of business ownership, is investigated on the level of unemployment in Japan. The question is to what extent business ownership, i.e., entrepreneurship, can reduce the level of unemployment. It will be concluded that Japan is hardly an outlier when using a simple model of the relationship between unemployment and the rate of business ownership. The model is calibrated using recent data of 23 OECD countries. It shows a minor underestimation of the rise in unemployment in Japan in the period 1984-2002. Arguments are brought forward why this might be the case. We argue that small firms in Japan have benefitted in the past from the protective environment of the keiretsu structure. In the current process of industrial restructuring, keiretsu support is dissipating, but has not yet been adequatly replaced with a market environment conducive to the establishment and growth of entrepreneurial firms. The underestimation of the rise in unemployment is a reflection of the limited access of small firms to the market in Japan.
Keywords: J60; L16; M13; O10; O53; 330; Entrepreneurship; business ownership; unemployment; industrial structure; Japan; Unternehmen; Eigentümerstruktur; Arbeitslosigkeit; Japan